Tubeimoside-1 affects the phenotype of skin squamous cell carcinoma SCL-1 cells by regulating the circ_0000376/miR-203 axis - Juan WANG; Chuncai XIAO; Xiaoyan QU; Chenyang ZHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To investigate the effect of tubeimoside-1 on the phenotype of skin squamous cell carcinoma SCL-1 cells and possible mechanism of action. Methods: SCL-1 cells were divided into the control group and the treatment groups, including different doses (5, 10, 20 μg/mL) of tubeimoside-1 groups, si-NC group, si-circ_0000376 group, tubeimoside-1+ pcDNA group, and tubeimoside-1+pcDNA-circ_0000376 group. CCK-8 method was used to detect cell proliferation inhibition rate.Transwell was used to detect cell migration and invasion. Flow cytometry was used to detect cell apoptosis. Western blot was used to detect the protein expression of Ki-67, MMP-2, MMP-9, Bcl-2 and Bax. RT-qPCR method was used to detect the expression of circ_0000376 and miR-203. The dual luciferase reporter gene experiment was used to verify the regulatory relationship between circ_0000376 and miR-203. Results: Compared with the control group, the proliferation inhibition rate, apoptosis rate and the Bax protein expression of cells in the tubeimoside-1 group were significantly increased (F=772.61, 352.20, 277.56, all P<0.01), while the number of cell migration and invasion, and Ki-67, MMP-2, MMP-9 and Bcl-2 protein expressions of cells in the tubeimoside-1 group were significantly decreased (F=125.57, 180.50, 257.87, 301.22, 399.27, 233.29, all P<0.01). The expression of circ_0000376 of cells in the tubeimoside-1 group was significantly lower than that in the control group (F=205.36, P<0.01), while the expression of miR-203 of cells in the tubeimoside-1 group was significantly higher than that in the control group (F=247.14, P<0.01), and the relation was dose-dependent. Compared with the si-NC group, the cell proliferation inhibition rate, apoptosis rate and the Bax protein expression of cells in si-circ_0000376 groups were significantly increased (t=36.78, 21.56, 25.20, all P<0.01), while the number of migration and invasion, and Ki-67, MMP-2, MMP-9 and Bcl-2 protein expressions of cells in si-circ_0000376 groups were significantly decreased (t=16.00, 17.79, 21.73, 21.02, 21.62, 19.68, all P<0.01). The results of dual luciferase reporter gene experiments showed that circ_0000376 could target miR-203. Compared with the tubeimoside-1+pcDNA group, the cell proliferation inhibition rate, apoptosis rate and the Bax protein expression of cells in the tubeimoside-1+pcDNA-circ_0000376 group were significantly decreased (t=35.31, 19.65, 19.55, all P<0.01), while the number of migration and invasion, and Ki-67, MMP-2, MMP-9 and Bcl-2 protein expression of cells in the tubeimoside-1+pcDNA-circ_0000376 group were significantly increased(t=12.27, 21.37, 24.15, 23.40, 23.48, 22.28, all P<0.01). Conclusion: Tubeimoside-1 may inhibit the proliferation, migration and invasion of skin squamous cell carcinoma cells and promote cells apoptosis by regulating circ_0000376/miR-203 axis.